2004
DOI: 10.1128/jb.186.5.1345-1354.2004
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Analysis of the Regulatory Genes in the Nystatin Biosynthetic Gene Cluster of Streptomyces noursei ATCC 11455 Reveals Their Differential Control Over Antibiotic Biosynthesis

Abstract: Six putative regulatory genes are located at the flank of the nystatin biosynthetic gene cluster in Streptomyces noursei ATCC 11455. Gene inactivation and complementation experiments revealed that nysRI, nysRII, nysRIII, and nysRIV are necessary for efficient nystatin production, whereas no significant roles could be demonstrated for the other two regulatory genes. To determine the in vivo targets for the NysR regulators, chromosomal integration vectors with the xylE reporter gene under the control of seven pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
79
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 40 publications
3
79
0
Order By: Relevance
“…However, because the mutation left some synthesis of erythromycin intact, it differs from deletions of activators in many streptomycetes that abolish the production of an antibiotic completely (3,23). Our observations more closely resemble the case of S. noursei, in which a strain with a deletion of a nystatin synthesis regulator still produced some antibiotic (24).…”
Section: Recombinant Bldd Binds To Ery Promoters and To Its Own Promosupporting
confidence: 56%
“…However, because the mutation left some synthesis of erythromycin intact, it differs from deletions of activators in many streptomycetes that abolish the production of an antibiotic completely (3,23). Our observations more closely resemble the case of S. noursei, in which a strain with a deletion of a nystatin synthesis regulator still produced some antibiotic (24).…”
Section: Recombinant Bldd Binds To Ery Promoters and To Its Own Promosupporting
confidence: 56%
“…The latter has been described for PKSI-encoding genes from the nystatin biosynthesis gene cluster of S. norsei. 7 In the case of S. viridochromogenes GW4-C1, no PCR fragment was obtained for aviM, aviGT3 and aviC2, whereas very tiny fragments Production of Avilamycin A Y Rebets et al were obtained for aviD, aviRa and aviC1 (Figure 2c). In the case of S. viridochromogenes GW4-C2, no PCR fragment was obtained for aviM, aviRa, aviGT3 and aviC2, whereas very tiny fragments were obtained for aviD and aviC1 (Figure 2d).…”
mentioning
confidence: 97%
“…[4][5][6] Recent efforts in cloning and characterization of biosynthetic gene clusters for new groups of secondary metabolites revealed novel classes of transcriptional factors that differ from typical SARPs or LAL representatives. 7,8 Avilamycins are secondary metabolites produced by Streptomyces viridochromogenes Tu57. They are active against Gram-positive bacteria.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that both gdmRI and gdmRII were positive regulatory genes of the geldanamycin biosynthesis. AveR [7] , RapH [8] , MonH [9] , PikD [10] , PimR [11] 以 及 NysRI 和 NusRII [12] 等, 它们与链霉菌抗生素调控蛋 …”
mentioning
confidence: 99%